Testing systemic fungicides for control of Phytophthora oak root disease. Issue 4 (13th March 2017) - González, M.; Caetano, P.; Sánchez, M. E.
Summary: Potassium phosphite (PP) formulations registered as fertilizers are now prohibited in Spain. Therefore, we evaluated the systemic fungicide fosetyl‐aluminium (fos‐al) in comparison with PP, against root rot caused by Phytophthora cinnamomi in Quercus woodlands. The direct effect of both systemic fungicides was evaluated in vitro on P. cinnamomi mycelial growth. Protection of cork and holm oak against infection was also evaluated in planta . Metalaxyl was included in both in vitro and in planta experiments for comparison purposes. At 100 μg/mL, PP totally inhibited colony radial growth, in comparison with 75% achieved by fos‐al. At doses recommended by manufacturers, with fos‐al and metalaxyl applications, root symptoms remained similar to the uninfected control levels. Based on these results, fos‐al is a candidate substitute product for PP in Quercus woodlands for control of Phytophthora oak root disease.